Literature Review on Longitudinal Study of Improving Numerical Literacy at Elementary Education - Moruk, Selviana; Sulisworo, Dwi (The Indonesian Institute of Science and Technology Research, 2024)
Numerical literacy is a fundamental skill in early childhood education, influencing later academic performance and cognitive development. A growing body of research has identified several factors that contribute to the development of numeracy skills, including home learning environments, executive function, socio-emotional skills, and socio-economic status. Understanding these factors is crucial for developing effective interventions that support children’s numeracy growth, especially in elementary education. This literature review synthesizes findings from longitudinal studies published between 2010 and 2024, focusing on the impact of home numeracy environments, executive function, socio-emotional skills, and socio-economic factors on early numeracy development. A total of five studies, with sample sizes ranging from small cohorts to large national samples, were analyzed. These studies employed longitudinal designs, assessing children over multiple years to capture the development of numeracy skills from preschool through elementary education. The review highlights the critical role of home learning environments, parental education, and socio-emotional skills in shaping children’s numeracy development. It also identifies bidirectional associations between cognitive and emotional skills, underscoring the need for integrated approaches to numeracy instruction. Socio-economic status was found to indirectly impact numeracy development, with home literacy and numeracy environments mediating this relationship. Long-term effects of early home-based learning on arithmetic fluency were also observed, emphasizing the importance of fostering supportive environments early in education. This review concludes that targeted interventions in home environments, as well as strategies that integrate cognitive and socio-emotional support, can significantly enhance numerical literacy outcomes in elementary education. Further research is needed to address gaps in understanding how these factors interact across diverse cultural and socio-economic contexts.